Malaga in the postcards of Purger & Co. around 1905. - Gámiz-Gordo, Antonio; Ruiz-Padrón, Luis (UMA Editorial, 2018)
The book includes an unpublished collection of more than 80 colorized postcards of Málaga printed by Purger & Co. around 1905. It analyzes the technical background and the context of these traveling images at the end of the nineteenth century, as a major cultural and commercial phenomenon. It also highlights their great value as documentary evidence of the urban landscape, architecture, and customs, offering original viewpoints that helped shape and disseminate an image of progress of the city at that time. This edition of the work is published in English.
Keywords: Málaga - En el arte; Tarjetas postales; Málaga; Purger & Co.; Paisaje; Progreso